Clinical efficacy and tolerability of praziquantel for intestinal and urinary schistosomiasis-a meta-analysis of comparative and non-comparative clinical trials. - Julien Zwang; Piero L Olliaro (PLoS Neglected Tropical Diseases)
Background Extensive use of praziquantel for treatment and control of schistosomiasis requires a comprehensive understanding of efficacy and safety of various doses for different Schistosoma species. Methodology/principal findings A systematic review and meta-analysis of comparative and non-comparative trials of praziquantel at any dose for any Schistosoma species assessed within two months post-treatment. Of 273 studies identified, 55 were eligible (19,499 subjects treated with praziquantel, control treatment or placebo). Most studied were in school-aged children (64%), S. mansoni (58%), and the 40 mg/kg dose (56%); 68% of subjects were in Africa. Efficacy was assessed as cure rate (CR, n=17,017) and egg reduction rate (ERR, n=13,007); safety as adverse events (AE) incidence. The WHO-recommended dose of praziquantel 40 mg/kg achieved CRs of 94.7% (95%CI 92.2-98.0) for S. japonicum, 77.1% (68.4-85.1) for S. haematobium, 76.7% (95%CI 71.9-81.2) for S. mansoni, and 63.5% (95%CI 48.2-77.0) for mixed S. haematobium/S. mansoni infections. Using a random-effect meta-analysis regression model, a dose-effect for CR was found up to 40 mg/kg for S. mansoni and 30 mg/kg for S. haematobium. The mean ERR was 95% for S. japonicum, 94.1% for S. haematobium, and 86.3% for S. mansoni. No significant relationship between dose and ERR was detected. Tolerability was assessed in 40 studies (12,435 subjects). On average, 56.9% (95%CI 47.4-67.9) of the subjects receiving praziquantel 40 mg/kg experienced an AE. The incidence of AEs ranged from 2.3% for urticaria to 31.1% for abdominal pain. Conclusions/significance The large number of subjects allows generalizable conclusions despite the inherent limitations of aggregated-data meta-analyses. The choice of praziquantel dose of 40 mg/kg is justified as a reasonable compromise for all species and ages, although in a proportion of sites efficacy may be lower than expected and age effects could not be fully explored.